In Vitro Antioxidant Activity of Stabilized Rice Bran and Its Fraction - Evy Damayanti; Fransiska Rungkat Zakaria; Hidayat Syarief; C Hanny Wijaya; Djoko Said Damardjati (Jurnal Teknologi dan Industri Pangan, 2004)
Some Researches indicated that oryzanol had antioxidant activity, however, the information about the oryzanol role in the prevention of low density lipoprotein (LDL) and human lymphocyte from oxidation under oxidative stress was still limited. The objective of this study was the investigate the antioxidant activity of oryzanol at concentrations based on rice bran beverage model in preventing LCL and lymphocyte from oxidation. Human plasma were supplemented with the samples of : rice bran oil (RBO), unsaponifiable matter and oryzanol IR-64, oryzanol IR-64 3x and oryzanol standard at the concentrations of 308.3, 22.2, 5.2, 10.4, and 10.4 Ã‚Âµg/ml, respectively. Afterward, the human LDL were collected by ultracentrifuge and diluted until a concentration of 200 Ã‚Âµg protein/ml was reached. Human LDL isolates were then oxidized with CuSO4 5 Ã‚ÂµM for measuring antioxidant activity of the sample. The length of incubation, H2O2 concentration, period of sample supplemented into human lymphocyte culture were determined before the antioxidant activity of RBO and its fraction in lymphocyte was measured. The samples used in the lymphocyte were RBO IR-64, unsaponifiable matter IR-64, and oryzanol standard at the concentrations of 133.2 – 2, 132.0 Ã‚Âµg/ml, 9.6 – 153.6 Ã‚Âµg/ml, and 2.4 – 37.7 Ã‚Âµg/ml, consecutively. The result showed that malonaldehyde concentration in human LDL decreased significantly (α = 0.05), 15 – 41% and 39 – 56% compared to the control. The absorbance of living lymphocyte cell in culture was not influenced by the type and concentration of RBO and its fraction. The addition of hydrogen peroxide (H2O2) 3 mM into culture sifnificantly lowered the absorbance as compared to culture without (H2O2). Key words :Oryzanol, oxidative stress, LDL-oxidized, lymphocyte and antioxidant activity.